[Petroscam ; Smokey Mountain - Lazaro, Cheche (Quezon City Probe Production, 1990)
A look at Joker Arroyo accusing Sec. Concepcion of DOTC of pressuring government banks to give " behest" loans. Also how the singing group was formed by Ryan Cayabyab and became a hit because their songs are of serials social issues. Includes also interviews with Geneva Cruz, James Coronel, Jeffrey and Tony.
Petroscam (18 min.) -- Smokey Mountain (19 min.)
VHS.
Keywords: Smokey Mountain (Singing Group).; Petroleum chemicals industry -- Philippines